Same as it ever was? The Aurignacian of the Swabian Jura and the origins of Palaeolithic art. (20th October 2018) - Floss, Harald
Abstract: The Aurignacian of the Swabian Jura constitutes a key region for the understanding of the behaviour of the first populations of modern humans in Europe. The region has yielded works of figurative art and musical instruments that are among the oldest in the world. The objects are evidence for the existence of a new type of society distinct from those known in previous phases of human prehistory. This article highlights the innovations intrinsic to the beginning of the Upper Palaeolithic and contests the idea of a gradual evolution, which erodes the clear distinction between the Middle Palaeolithic and the Upper Palaeolithic at some point in the transition.